The antioxidant peptide salamandrin-i: First bioactive peptide identified from skin secretion of salamandra genus (salamandra salamandra) - Plácido, Alexandra; Bueno, João; Barbosa, Eder A.; Moreira, Daniel C.; Dias, Jhones Do Nascimento; Cabral, Wanessa Felix; Albuquerque, Patrícia; Bessa, Lucinda J.; Freitas, Jaime; Kuckelhaus, Selma A. S.; Lima, Filipe C. D. A.; Batagin-Neto, Augusto [UNESP]; et al. (MDPI, 2020)
Amphibian skin is a multifunctional organ that plays key roles in defense, breathing, and water balance. In this study, skin secretion samples of the fire salamander (Salamandra salamandra) were separated using RP-HPLC and de novo sequenced using MALDI-TOF MS/MS. Next, we used an in silico platform to screen antioxidant molecules in the framework of density functional theory. One of the identified peptides, salamandrin-I, [M + H]+ = 1406.6 Da, was selected for solid-phase synthesis; it showed free radical scavenging activity against DPPH and ABTS radicals. Salamandrin-I did not show antimicrobial activity against Gram-positive and-negative bacteria. In vitro assays using human microglia and red blood cells showed that salamandrin-I has no cytotoxicity up to the concentration of 100 µM. In addition, in vivo toxicity tests on Galleria mellonella larvae resulted in no mortality at 20 and 40 mg/kg. Antioxidant peptides derived from natural sources are increasingly attracting interest. Among several applications, these peptides, such as salamandrin-I, can be used as templates in the design of novel antioxidant molecules that may contribute to devising strategies for more effective control of neurological disease.
Keywords: Antioxidant peptides; Bioactive molecules; Portuguese biodiversity; Salamandra salamandra